Factors affecting amplang production in Samarinda City, East Kalimantan Province - Augusta, Yanisa; Haqiqiansyah, Gusti; Fahrizal, Wahyu (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
This study uses several factors of production, namely capital, labor (HOK), and raw materials. The aims of this study were: (1) to determine the influence of production factors such as capital, labor (HOK) and raw materials; and (2) to find out what problems or obstacles are experienced during running a business. This research was conducted in Samarinda City, East Kalimantan Province. Primary data is obtained by observing and recording (observation) directly at the research location/object to be studied, as well as using direct interview techniques with respondents, namely business owners/employees. The sampling method for this research was carried out using a purposive sampling method, the samples selected based on these criteria were 30 businessmen processing amplangs/respondents. Methods of data analysis in this study used: (1) multiple linear regression analysis; (2) statistical test; (3) classic assumption test; and (4) descriptive analysis using computerized calculation tools such as Microsoft Excel Software and SPSS (Statistical Product And Service Solutions). The results showed that: Simultaneously (together), the capital input variable (X1), labor input (HOK) (X2) and raw material input (X3) had a significant effect on the amplang production variable (Yi), while partially, only labor input (HOK) (X2) and raw material input (X3) had a significant effect on the amplang production variable (Yi). The problems experienced by amplang processors were a decline in sales during the Covid-19 pandemic and a lack of availability of fish raw materials.